2020
DOI: 10.3390/vetsci7010029
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices Regarding Rabies in El Jadida Region, Morocco

Abstract: The aim of this study was to evaluate the knowledge, attitudes, and practices regarding rabies in the El Jadida region, Morocco. We conducted a cross-sectional survey using a structured questionnaire among randomly selected residents across 24 study sites. In total, 407 respondents took part in the survey. The majority (367, 92%) were male and had no formal education (270, 66%). Some (118, 29%) believed that rabies does not affect humans. Most respondents (320, 79%) were aware that vaccination could prevent ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 29 publications
(45 reference statements)
8
21
0
Order By: Relevance
“…The findings from our study revealed that the respondents had a negative attitude towards stray dogs, as they believed that a high density of stray dogs was the main obstacle for rabies prevention and control and that culling could be the best choice to control the dog population. The findings were consistent with another study conducted by Bouaddi et al [ 34 ] who reported that 45% of the respondents in the survey did not agree to dog sterilisation and 54.3% provided their opinion in favour of culling. Regular vaccination of dogs and well-planned sterilisation methods could reduce rabies transmission and dog population in the community [ 19 , 43 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings from our study revealed that the respondents had a negative attitude towards stray dogs, as they believed that a high density of stray dogs was the main obstacle for rabies prevention and control and that culling could be the best choice to control the dog population. The findings were consistent with another study conducted by Bouaddi et al [ 34 ] who reported that 45% of the respondents in the survey did not agree to dog sterilisation and 54.3% provided their opinion in favour of culling. Regular vaccination of dogs and well-planned sterilisation methods could reduce rabies transmission and dog population in the community [ 19 , 43 ].…”
Section: Discussionsupporting
confidence: 92%
“…The findings correspond to a study conducted by Alam et al [ 20 ] who reported that 58% of people were unaware about the rabies, while over one-third of the respondents among the CPs were unaware about the consequences of the disease. The findings were consistent with another study conducted in Ethiopia (67.8%) [ 22 ], but the results were higher than the findings obtained from a study conducted in Morocco (10.2%) [ 34 ].…”
Section: Discussionsupporting
confidence: 90%
“…This is of great concern since it would prove fatal if bitten by a rabid dog. Most of the human mortalities in rabies endemic countries occur following inefficient health-seeking behaviors by dog bite victims, who cannot, or do not want to, access appropriate medical treatment and resort to local treatments [ 4 , 19 , 21 , 33 , 34 ]. Furthermore, the students in our survey mentioned that they would try to catch and take a sick dog to a veterinary hospital for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This ignorance is of significant public health concern. The percentage of respondents who were unaware of the best first course of action after being bitten by a dog in our study is higher compared to other countries such as Bangladesh (2%), Cameroon (18%), and Ethiopia (30.7%) [ 18 ].…”
Section: Discussionmentioning
confidence: 64%